Synthesis and deposition of a Tröger's base polymer on the electrode surface for potentiometric detection of a neuroblastoma tumor marker metabolite. Issue 80 (19th September 2016) - Shishkanova, T. V.; Havlík, M.; Dendisová, M.; Matějka, P.; Král, V.
Abstract : We propose an innovative approach to detect a low molecular weight metabolite of neuroblastoma. Abstract : The development of novel diagnostic tools is a primary goal in bioanalytical chemistry. Here we report the synthesis of Tröger's base functionalized with amino- and coumarin-units designed as a monomeric unit for the development of an electrochemical cancer sensor. The synthesized receptor was deposited onto a conducting support using electrochemical polymerization, characterized spectroscopically and tested potentiometrically towards metabolites used as tumor markers of neuroblastoma.